Upaya Pencegahan Kekerasan Seksual Melalui Pendidikan Islam di Perguruan Tinggi Muhammadiyah - Asrori Mukhtarom; Desri Arwen; Nur Afif (Ikatan Dai Indonesia, 2026)
Sexual violence is a serious problem that frequently occurs on campuses. This problem has negative physical and psychological impacts on victims, such as trauma, depression, and injuries to intimate areas. Several factors contribute to the occurrence of sexual violence, such as power relations, lax law enforcement against perpetrators, a lack of awareness of the dangers of sexual violence, and the perpetrator's inability to control sexual desires. Maximum efforts are needed to prevent sexual violence so that campuses become safe and comfortable places for students to study. This study aims to determine the efforts made by Muhammadiyah universities to prevent sexual violence through an Islamic education approach. This type of research uses qualitative research. In collecting data, the researcher used observation, interviews, and documentation techniques. Data analysis used data reduction, data presentation, and drawing conclusions. The research location is Muhammadiyah University, Tangerang. The results show efforts made by Muhammadiyah universities to prevent sexual violence through Islamic education by incorporating Islamic education content into the curriculum of undergraduate and master's programs in the form of Al-Islam and Muhammadiyah courses. Further efforts include implementing Islamic guidance for all institutional leaders, lecturers, and staff on campus. Furthermore, they implemented Islamic-based programs, such as Quran memorization programs for the entire campus community and seminars on the dangers of sexual violence. These efforts have been highly effective in preventing sexual violence on campus.